AUTOMATED CONTROL SYSTEM IN GREENHOUSE WITH NEURAL NETWORK PREDICTIONS OF EXTERNAL DISTURBANCES - Dudnyk, A. (Energy and Automation, 2015)
Efficiency of creation automation control system in a greenhouse with using solar radiation intensity and temperature predictions by neural networks is shown.